2018
DOI: 10.1371/journal.pone.0208977
|View full text |Cite
|
Sign up to set email alerts
|

Guinea pig immunoglobulin VH and VL naïve repertoire analysis

Abstract: The guinea pig has been used as a model to study various human infectious diseases because of its similarity to humans regarding symptoms and immune response, but little is known about the humoral immune response. To better understand the mechanism underlying the generation of the antibody repertoire in guinea pigs, we performed deep sequencing of full-length immunoglobulin variable chains from naïve B and plasma cells. We gathered and analyzed nearly 16,000 full-length VH, Vκ and Vλ genes and analyzed V and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This might explain the contradictory data previously published by Vassilieva et al, in which flagellin functionalization enhanced the Env-specific humoral responses to Env-VLP immunization in guinea pigs [28]. Guinea pigs are phylogenetically distant from mice and have higher immunoglobulin combinatorial diversity [31]. These animals are broadly used in HIV studies due to their ability to induce HIV-Env neutralizing antibodies [32], which might indicate a stronger immunogenicity of HIV-Env in guinea pigs than in mice.…”
Section: Resultsmentioning
confidence: 99%
“…This might explain the contradictory data previously published by Vassilieva et al, in which flagellin functionalization enhanced the Env-specific humoral responses to Env-VLP immunization in guinea pigs [28]. Guinea pigs are phylogenetically distant from mice and have higher immunoglobulin combinatorial diversity [31]. These animals are broadly used in HIV studies due to their ability to induce HIV-Env neutralizing antibodies [32], which might indicate a stronger immunogenicity of HIV-Env in guinea pigs than in mice.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that guinea pigs can be a novel source of monoclonal antibodies. Because guinea pigs have a completely different B-cell repertoire than mice, this animal may offer novel solutions for the production of high-affinity antibodies against CoV-2-NP that cannot be produced in mice [ 14 , 15 ]. In this study, we developed mAbs from guinea pigs immunized with CoV-2-NP and selected highly specific epitope-characterized mAbs suitable for the detection of CoV-2-NP.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that guinea pigs can be a novel source of monoclonal antibodies. Because guinea pigs have a completely different B-cell repertoire than mice, this animal may offer novel solutions for producing high-a nity antibodies against CoV-2-NP that cannot be produced in mice [13] [14]. In this study, we developed mAbs from guinea pigs immunized with CoV-2-NP and highly speci c epitope-characterized mAbs suitable for the detection of CoV-2-NP were selected.…”
mentioning
confidence: 99%